Still excluded? An update on the status of African American Scholars in the discipline of Criminology and Criminal Justice - Gabbidon, Shaun L. (Journal of research in crime and delinquency, 2004)
This article reexamines the exclusion of African Americans in the discipline of criminology and criminal justice. Young and Sulton raised this issue in their important article that focused on the role of African American scholars in various aspects of the field. The article revisits several areas investigated in the original article, including the integration of African American scholarship in assorted scholarly outlets, race of editorial board members of the major criminal justice journals, race of grant recipients, use of African American criminologists as experts for media stories, and as consultants in the policymaking process. In addition, the authors' analysis examines criminology and criminal justice programs at historically Black colleges and universities. The results from these analyses show moderate progress within the past decade. Nevertheless, the authors conclude that in the next decade, much more needs to be accomplished in many of the areas examined to facilitate the integration of African Americans in criminology and criminal justice and to ensure that gains that have been made are not lost